2021
DOI: 10.3390/molecules26092769
|View full text |Cite
|
Sign up to set email alerts
|

Honey Phenolic Compound Profiling and Authenticity Assessment Using HRMS Targeted and Untargeted Metabolomics

Abstract: Honey consumption is attributed to potentially advantageous effects on human health due to its antioxidant capacity as well as anti-inflammatory and antimicrobial activity, which are mainly related to phenolic compound content. Phenolic compounds are secondary metabolites of plants, and their content in honey is primarily affected by the botanical and geographical origin. In this study, a high-resolution mass spectrometry (HRMS) method was applied to determine the phenolic profile of various honey matrices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 86 publications
3
40
0
Order By: Relevance
“…It is related to plant protection against dryness and environmental stress. Abscisic acid has been found in many types of honey (heather, rapeseed, lime-tree, Robinia, Leptospermum and sunflower) in different amounts [ 12 , 53 , 54 ]. It was detected in high amounts (13.93–23.03 mg/kg) in the samples collected from the southern part of Romania; we observed that high temperature in the season, as well as dryness (lack of humidity), was a determinant for the quantified amounts, while samples collected from inside the Transylvania (hilly region, with more humidity; presented in Material and Methods section), presented lower amounts of abscisic acid (2.95–6.61 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…It is related to plant protection against dryness and environmental stress. Abscisic acid has been found in many types of honey (heather, rapeseed, lime-tree, Robinia, Leptospermum and sunflower) in different amounts [ 12 , 53 , 54 ]. It was detected in high amounts (13.93–23.03 mg/kg) in the samples collected from the southern part of Romania; we observed that high temperature in the season, as well as dryness (lack of humidity), was a determinant for the quantified amounts, while samples collected from inside the Transylvania (hilly region, with more humidity; presented in Material and Methods section), presented lower amounts of abscisic acid (2.95–6.61 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…The generally accepted melissopalynological analysis, the examination of these parameters provides a more precise assessment of the botanical and geographical origins of the honey (15,22). A very useful tool for distinguishing honey samples is also statistical analysis (8,23,24). Considering taste to be crucial for honey consumption, sensory analysis is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…All identified compounds showed high mass accuracy, below 2 mDa, isotoping fitting below 50 mSigma and retention time (tR) tolerance below 0.2 min. Especially for isokaempferide and tectochrysin, which were not included in our previous suspect screening workflow [ 12 ], their identification was accomplished by comparing experimental MS/MS fragments with MS/MS spectra found in the mass spectral library MassBank of North America. Additionally, differences between the experimental and predicted tR were considered.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the discussed facts, we analyzed a total of 169 honey samples with different botanical origins, namely blossom ( n = 62) and the unifloral fir ( n = 10), oak ( n = 24), pine ( n = 39) and thyme ( n = 34) honeys to reveal botanical origin markers of Greek honey through their phenolic compound content. To achieve that, our recently developed ultra-high-performance liquid chromatography hybrid quadrupole time-of-flight mass spectrometry (UHPLC-q-TOF-MS) method [ 12 ] was verified, and the analyte target list was updated, including a total of 24 target phenolic compounds. Besides targeted metabolomics, suspect and non-targeted workflows were also utilized.…”
Section: Introductionmentioning
confidence: 99%